2017
DOI: 10.1007/s10530-017-1637-4
|View full text |Cite
|
Sign up to set email alerts
|

Plant neighbour identity and invasive pathogen infection affect associational resistance to an invasive gall wasp

Abstract: Theory predicts that mixed forests are more resistant to native pests than pure forests (i.e. associational resistance) because of reduced host accessibility and increased top-down control by natural enemies. Yet, whether the same mechanisms also apply to invasive pests remains to be verified. We tested the hypothesis of associational resistance against the invasive Asian chestnut gall wasp (ACGW, Dryocosmus kuriphilus) by comparing ACGW infestation rates on chestnuts (Castanea sativa) in stands varying in spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 98 publications
(120 reference statements)
1
18
0
Order By: Relevance
“…Although we cannot exclude that other stand characteristics such as stem density or species mixture may influence the impact of a pest such as the ACGW (e.g. Fernandez-Conradi et al, 2018), we strongly recommend an immediate release of the antagonist since the first ACGW appearance. This will allow to avoid repeated ACGW attacks that pose a threat for chestnut coppices devoted to high-quality wood production because of the abrupt reductions in radial growth that usually increase the risk of ring-shake (Fonti & Macchioni, 2003;Fonti & Sell, 2003;Spina & Romagnoli, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although we cannot exclude that other stand characteristics such as stem density or species mixture may influence the impact of a pest such as the ACGW (e.g. Fernandez-Conradi et al, 2018), we strongly recommend an immediate release of the antagonist since the first ACGW appearance. This will allow to avoid repeated ACGW attacks that pose a threat for chestnut coppices devoted to high-quality wood production because of the abrupt reductions in radial growth that usually increase the risk of ring-shake (Fonti & Macchioni, 2003;Fonti & Sell, 2003;Spina & Romagnoli, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Jactel & Brockerhoff, 2007). Earlier observations of less damage by D. kuriphilus in stands with higher tree diversity (Fernandez‐Conradi et al., 2018; Guyot et al., 2015) also support this hypothesis.…”
Section: Discussionmentioning
confidence: 63%
“…The cold treatment did not affect the composition of the parasitoid community in any chestnut field, which is congruent with what reported by [75], who did not found differences in diversity, richness, or evenness of ACGW-associated species despite differences in their habitat. Conversely, [76] showed that native parasitoid communities emerging from galls differed between pure and mixed chestnut stands at the same altitude, even if there was no difference in their abundance.…”
Section: Discussionmentioning
confidence: 92%